Potential Benefits of Jujube (Zizyphus Lotus L.) Bioactive Compounds for Nutrition and Health - Souleymane Abdoul-Azize (Journal of Nutrition and Metabolism)
Zizyphus lotus, belonging to the Rhamnaceae family, is a deciduous shrub which generally grows in arid and semiarid regions of the globe. In traditional medicine, Z. lotus is used as antidiabetes, sedative, bronchitis, and antidiarrhea by local populations. Recently, several scientific reports for health benefit and nutritional potential of bioactive compounds from this jujube have been reported. This plant is rich in polyphenols, cyclopeptide alkaloids, dammarane saponins, vitamins, minerals, amino acids, and polyunsaturated fatty acids. These identified compounds were supposed to be responsible for most of Z. lotus biologically relevant activities including antimicrobial, anti-inflammatory, hypoglycemic, antioxidant, and immunomodulatory effects. The aim of the present review was to give particular emphasis on the most recent findings on biological effects of the major groups of Zizyphus lotus components and their medical interest, notably for human nutrition, health benefit, and therapeutic impacts.